A Preliminary Assessment of Bird Communities and Their Conservation Status in Two Grand Forest Parks (Tahura) of Lamandau, Central Kalimantan - Patanduk, Adolfina; Wicaksono, Gusti; Rahmawati, Niken; Sunarto, Sunarto; Widaryo, Iwan; Sapari, Iman (Journal of Tropical Biodiversity, 2025)
In 2023, the Environment and Forestry Service (DLHK) of Lamandau Regency, Central Kalimantan, designated two forest areas, Tahura Bukit Selajaan and Tahura Bukit Benyawai, as Grand Forest Parks (Tahura) to strengthen biodiversity conservation and management efforts. This preliminary study aimed to inventory bird species, analyze species composition and community structure, and identify protected and endangered species in both areas. The research employed line transect and point count methods, supported by camera traps to enhance detection. A total of 92 bird species were recorded, including 21 protected and 9 endangered species. The Sørensen Similarity Index (>75%) indicated a high degree of similarity in bird communities between the sites, suggesting comparable habitat conditions. Key species such as the Bornean Bristlehead, Helmeted Hornbill, Rhinoceros Hornbill, and Great Argus highlight significant avitourism potential. These findings provide a crucial baseline for sustainable conservation planning. However, ongoing anthropogenic pressures threaten habitat quality. Strategies such as public awareness programs, regular monitoring and patrols, and the development of conservation based alternative livelihoods are essential to ensure long term ecological integrity and sustainable management of the Tahura areas.